Entrepreneurial ecosystems and regional persistence of high growth firms: A ‘broken clock’ critique - Coad, Alex; Srhoj, Stjepan (Research Policy, 2023)
: The Entrepreneurial Ecosystems (EE) approach makes specific predictions regarding how EE inputs are converted into high-growth firms (HGFs) as an output. A simulation model draws out our hypothesis of regional persistence in HGF shares. Based on intuitions that EEs are persistent, we investigate whether regional HGF shares are persistent, using census data for 2 European countries taken separately (Croatia for 2004-2019, and Slovenia for 2008-2014). Overall, there is no clear persistence in regional HGF shares - regions with large HGF shares in one period are not necessarily likely to have large HGF shares in the following period. This is a puzzle for EE theory. In fact, there seems to be more persistence in industry-level HGF shares than for regional HGF shares. We formulate a ‘ broken clock ’ critique - just as a broken clock is correct twice a day, EE recommendations may sometimes be correct, but are fundamentally flawed as long as time-changing outcomes (HGF shares) are predicted using time-invariant variables (such as local universities, institutions and infrastructure).